Baseline on rare earth elements in the marine sediments of a Mediterranean commercial port as environmental tracers and their relationships with inorganic contaminants. (December 2021) - Consani, Sirio; Cutroneo, Laura
Abstract: The Port of Genoa (north-western Mediterranean Sea) receives sediments from two different catchment areas (Bisagno and Polcevera torrents). The aim of the work is to evaluate if Rare Earth Elements (REEs) could be used to identify the two sedimentary inputs and to unravel the origin of inorganic contaminants in an anthropised basin. REE results constitute a baseline for this port. The main REE-bearing minerals are phosphates and zircon. As, Cd, Hg, Pb, and Sn concentrate in the sediments closer to the Bisagno Torrent mouth, and the correlation with Ca and Light-REEs suggests their plausible geological origin. Co, Mn, and Ni maxima lie in the sediments closer to the Polcevera Torrent. Their correlation with Middle-REEs and Mg suggest that ophiolitic rocks could explain their presence. Cr, Cu, V, and Zn do not show a clear correlation with REEs, and their origin probably is a combination of natural and anthropogenic sources. Highlights: The data reported in this paper are a REE-baseline for the Port of Genoa (Italy). REEs allow to infer the origin of inorganic contaminants in the bottom sediments. As, Cd, Hg, Sn, and Pb seem related to the sediment carried by the Bisagno Torrent Co, Mn, and Ni derive from the ophiolitic rock sediments of the Polcevera Torrent Cr, Cu, V, and Zn concentration is the results of natural and anthropic sources.